- Heterogeneous Fleet Vehicle Routing Problem dan Penyelesaiannya Menggunakan Metode Nearest Neighbor : Kasus Pendistribusian Ayam Potong - Evi Yuliza; Novi Rustiana Dewi; Sisca Octarina; Indrawati Indrawati (Limits: Journal of Mathematics and Its Applications, 2026)
Distribution of goods using a heterogeneous fleet of vehicles is an important aspect in a logistics system because it affects distribution efficiency. This study aims to determine the optimal distribution route for broiler chickens using the Heterogeneous Fleet Vehicle Routing Problem (HFVRP) model to minimize the total vehicle mileage. The data used include customer locations, number of requests, vehicle capacity, heterogeneous vehicle types, and distances between locations. The problem is modeled in HFVRP by considering vehicle capacity, each customer is visited exactly once, and vehicles depart and return to the depot. The solution is carried out using the Nearest Neighbor method to generate distribution routes and compared with the optimal solution from the HFVRP model. The results show a total mileage of 88.6 km for the Nearest Neighbor method, while the optimal solution from the HFVRP model produces a total mileage of 121.2 km. Based on these results, the Nearest Neighbor method provides a more efficient route solution in the case of broiler chicken distribution.